Knowledge-based economy in Central and East European countries. Countries and industries in a process of change - Piech, Krzysztof; Radosevic, Slavo (New York, 2006)
"After successful transition from a socialist to market economy, the countries of Central and Eastern Europe are faced with the challenge of how to catch up with the EU15. This book provides the first systematic analysis of how Central and Eastern Europe has been restructuring from a knowledge-based economy perspective. It is an essential reference for understanding processes that are shaping present and future growth of the eastern part of the enlarged EU."